Online Implementation of Marriage Management Information System (SIMKAH) to Improve Service Quality - Aditya, Aditya; Adi Wardana, Wahyu Satya (MILRev: Metro Islamic Law Review, 2022)
This Scientific Writing contains the application of an online Marriage Management Information System (SIMKAH) to improve service quality. The research method used in this paper is normative legal research, which uses secondary or library data. The results of this study indicate that the application of a web-based online Marriage Management Information System (SIMKAH) at KUA is a form of modernizing marriage registration which is usually done manually in the KUA sub-district in serving the community. However, it is still not optimal because servers and networks often experience interruptions, which affect application speed. The implementation of the urgency system is an effort to support the implementation of government programs in maximizing IT-based services to the community and assisting KUA officers in the fields of marriage registration, marriage registration, marriage examinations, same marriages, and reconciliation. The quality of the information generated from the system is relevant to the needs and the output is complete and can be directly felt by users of the system and the community as recipients of the information, in this case, the procedure for recording which is usually done in writing by the administrator, can be typed into the SIMKAH program and operated by the administrator. itself so that the shape of the NB, N, and NA models can be printed/printed, and is more effective than writing. However, not all KUA apply SIMKAH optimally. As for the application of SIMKAH, it has followed the Instructions of the Director General of Islamic Community Guidance Number DJ.II/369 of 2013 concerning implementing the Marriage Management Information System (SIMKAH) at the Sub-District KUA.